PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MEDIA TABEL DENGAN POWER POINT PADA SISWA SEKOLAH DASAR - Sapartien, Retno (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
The purpose of this study was to determine the effectiveness of the use of media "Table" withPower Point in mathematics learning material determine the greatest common factor and leastcommon multiple in improving learning outcomes of learners and to determine changes inlearning behavior. Using the method of action research consisted of two cycles and each cycle tofollow the stages of planning, implementation of the action, observations, and reflection with datacollection using observation, testing, and documentation. The results of the study in cycle 1 theaverage value of 76 students, with 19 students completed and there are 6 learners unfinished.While on the second cycle of the average value increased to 88 to 22 students completed and 3learners still unresolved. Utilization of media tables in love with the variation applicationPowerPoint more effectively to instill the concept of how to determine the FPB and theCommission in learning mathematics in fourth grade elementary school Bonangrejo first half ofthe school year 2015/2016.